Emerging Trends in Global Lung Cancer Burden - Shong, Lynn Y.-W.; Lam, David C.-L. (Seminars in Respiratory and Critical Care Medicine, 2025)
Lung cancer remains the leading cause of cancer-related deaths worldwide, with its burden shaped by evolving risk factors, demographic changes, and healthcare disparities. Over the past decades, while age-standardized incidence and mortality rates have declined, the absolute number of cases has risen due to population growth and aging. Tobacco smoking remains the most common risk factor, accounting for approximately 60% of cases globally, though its contribution has declined in high-income regions due to effective tobacco control. Conversely, countries with lower socioeconomic development, particularly in East and South Asia, face rising incidence and mortality driven by increasing smoking prevalence, air pollution, and limited access to healthcare. Emerging risk factors, such as ambient air pollution and genetic predisposition, are increasingly significant, particularly in regions with lower Human Development Index scores. Sex disparities are evident, with lung cancer rates declining among men in many high-income countries but rising among women globally. Early-onset lung cancer is also an emerging concern, especially in middle socio-demographic index regions, driven by smoking, environmental exposures, and genetic factors. By 2035, it is predicted that lung cancer deaths could reach 3 million annually. To address the impact of the growing lung cancer burden, a multifaceted approach is needed, including strengthened tobacco control, improved air quality, promotion of clean cooking fuels, and expanded low-dose computed tomography screening, particularly in resource-constrained regions.
Keywords: lung cancer; epidemiology; smoking; air pollution; early-onset lung cancer; global cancer trends